Neglected experiences: Fertility and childbearing among young people in Ethiopia - Chuta, N (Young Lives, 2021)
This policy brief draws on a qualitative study of young people in eight rural and urban communities who are part of the Young Lives longitudinal study of 3,000 children and young people in Ethiopia.